The effectiveness of the use of educational aids in achieving the goals of the subject of education and sports - tahir yasmin,; adel zaouak,; cherifi_messaoud, (sports creativity, 2025)
The present study aims at demonstrating the effectiveness of the use of teaching aids in achieving the objectives of physical and sports education in the secondary stage. On the effectiveness of the use of teaching aids in achieving the objectives of physical education and sports secondary stage, the sample was randomly selected, and on this basis we selected a sample consisting of 30 professors located in secondary schools of the Wilayat of Algeria east, and through In this regard, we have relied on the opinions of the applied professors, and in the light of the results of the study, and the statistical treatment of the questionnaire, we concluded that: Professor of physical education and sports have a role in the use of teaching aids, teaching aids available in the secondary contribute to the success of physical education classes and sports, not to exploit educational means In an appropriate way hinders the good functioning of physical education and sports classes